2004
DOI: 10.1242/dev.00938
|View full text |Cite
|
Sign up to set email alerts
|

RABBIT EARS, encoding a SUPERMAN-like zinc finger protein,regulates petal development inArabidopsis thaliana

Abstract: There was an error published in Development 131, 425-434.On page 428, the description of the rbe-1 mutation and its position as depicted in Fig. 2B were incorrect. The correct description is as follows. In rbe-1, a C to T transversion at nucleotide position 241 in the cDNA sequence results in the replacement of an arginine with a stop codon at amino acid 81 in the RBE protein.The authors apologise to readers for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(90 citation statements)
references
References 45 publications
1
89
0
Order By: Relevance
“…In silico analysis revealed that there are 176 C2H2-type zinc finger proteins in Arabidopsis, from which 33 are conserved in other eukaryotes and 143 appear to be plant specific (Englbrecht et al, 2004). Members of this gene family have been implicated in the regulation of plant development, including photomorphogenesis, leaf, shoot, and flower organogenesis, gametogenesis, seed development, and dormancy (Sakai et al, 1995;Chrispeels et al, 2000;Prigge and Wagner, 2001;Dinkins et al, 2002;He and Gan, 2004;Ohno et al, 2004;Takeda et al, 2004). Our data show that ZFP3 and its closest C2H2-type zinc-finger protein homologs (ZFPs) are negative regulators of ABA signaling during germination, influence vegetative development and fertility, and modulate red light signaling in seedling photomorphogenesis.…”
mentioning
confidence: 66%
“…In silico analysis revealed that there are 176 C2H2-type zinc finger proteins in Arabidopsis, from which 33 are conserved in other eukaryotes and 143 appear to be plant specific (Englbrecht et al, 2004). Members of this gene family have been implicated in the regulation of plant development, including photomorphogenesis, leaf, shoot, and flower organogenesis, gametogenesis, seed development, and dormancy (Sakai et al, 1995;Chrispeels et al, 2000;Prigge and Wagner, 2001;Dinkins et al, 2002;He and Gan, 2004;Ohno et al, 2004;Takeda et al, 2004). Our data show that ZFP3 and its closest C2H2-type zinc-finger protein homologs (ZFPs) are negative regulators of ABA signaling during germination, influence vegetative development and fertility, and modulate red light signaling in seedling photomorphogenesis.…”
mentioning
confidence: 66%
“…It is not surprising, however, for a boundary gene to control cell proliferation, as cell division rates are lower at boundaries, including the boundary between stamens and carpels, than in developing organs (2,26). For instance, RABBIT EARS (RBE), which encodes a C2H2 zinc-finger protein related to SUP, specifies the boundary between whorls 2 and 3 by excluding AG from whorl 2 (27,28), and also specifies the intersepal boundaries by regulating cell proliferation in whorl 1 via the miR164/CUP-SHAPED COTYLEDON (CUC) module (29).…”
Section: Discussionmentioning
confidence: 99%
“…4B). We also studied the effect of transfer DNA insertions within binding sites located in the vicinity of the floral regulators UN-USUAL FLORAL ORGANS (UFO) (28) and RABBIT EARS (RBE) (29), which respond transcriptionally to the perturbation of B function (Fig. 2F).…”
Section: Time After Treatment Start [H] Normalized Expressionmentioning
confidence: 99%